Model of Determining Business Performance of Women's MSMEs in Medan City - Astuti, Rini; Tanjung , Hasrudy (Universitas Muhammadiyah Sorong, 2024)
The performance of a female entrepreneur is measured by several factors. The intelligence factor which is a combination of several intelligences including intellectual intelligence, emotional intelligence and spiritual intelligence is the right combination of intelligence and really helps women's entrepreneurial behavior in running their business. Businesswomen need the right combination of intellectual intelligence, emotional intelligence and good spiritual intelligence to be able to build their motivation and commitment to become entrepreneurs which will have a better impact on their performance as businesspeople, so this research aims to determine the role of entrepreneurs. intellectual intelligence, emotional intelligence and spiritual intelligence on the performance of women entrepreneurs as MSMEs in the city of Medan. This research aims to test and determine the intelligence factors that influence the performance of women in the city of Medan. The population in this study were all female MSME actors in Medan City and the sample size of the researchers took data from a sample of at least 100 MSMEs. The data analysis method uses Confirmatory Factor Analysis (CFA) to detect antecedent variables using the structural equality model SEM (Structural Equation Model). The research results show that intellectual intelligence and spiritual intelligence have an influence, while emotional intelligence has no effect on women's performance in MSMEs.